Germ cell and tumor associated piRNAs in the medaka and Xiphophorus melanoma models. (December 2016) - Kneitz, Susanne; Mishra, Rasmi R.; Chalopin, Domitille; Postlethwait, John; Warren, Wesley C.; Walter, Ronald B.; Schartl, Manfred
Abstract Background A growing number of studies report an abnormal expression of Piwi-interacting RNAs (piRNAs) and the piRNA processing enzyme Piwi in many cancers. Whether this finding is an epiphenomenon of the chaotic molecular biology of the fast dividing, neoplastically transformed cells or is functionally relevant to tumorigenesisis is difficult to discern at present. To better understand the role of piRNAs in cancer development small laboratory fish models can make a valuable contribution. However, little is known about piRNAs in somatic and neoplastic tissues of fish. Results To identify piRNA clusters that might be involved in melanoma pathogenesis, we use several transgenic lines of medaka, and platyfish/swordtail hybrids, which develop various types of melanoma. In these tumors Piwi, is expressed at different levels, depending on tumor type. To quantify piRNA levels, whole piRNA populations of testes and melanomas of different histotypes were sequenced. Because no reference piRNA cluster set for medaka orXiphophorus was yet available we developed a software pipeline to detect piRNA clusters in our samples and clusters were selected that were enriched in one or more samples. We found several loci to be overexpressed or down-regulated in different melanoma subtypes as compared to hyperpigmented skin. Furthermore, cluster analysis revealed a clear distinction between testes, low-grade and high-grade malignant melanoma in medaka. Conclusions Our data imply that dysregulation of piRNA expression may be associated with development of melanoma. Our results also reinforce the importance of fish as a suitable model system to study the role of piRNAs in tumorigenesis.